ANALYSIS OF FOREIGN EXPERIENCE OF EFFECTIVE MANAGEMENT OF COMPANY BRANDS: MODERN REGULATORY AND LEGAL MODELS OF BRAND MANAGEMENT - Крахмальова, Тетяна А. (Journal of Strategic Economic Research, 2023)
The article presents the results of a study of the foreign experience of brand formation, provides an analysis of models of effective management and protection of intellectual property rights to it. The analysis of foreign experience of effective management of company brands and modern brand management models was carried out. Thus, the foreign experience of successful brand management is presented in terms of two models: Anglo-American or Western and Japanese or Eastern. Distinguishing these two models are logical differences in macroeconomic development and traditions of management – American and Japanese. It has been proven that, despite a rather variable number of international legal acts, international law lacks uniform conditions-criteria for the use of a brand for the purpose of preserving exclusive rights to it; lack of unified methods for evaluating the similarity of brands. The overall brand strategy, group, product, price, brand identification strategy and brand communication strategy were analyzed and the leading innovative branding strategies were substantiated accordingly. It has been established that in order to counteract the aggressive and oversaturated market environment with various goods and services, under the modern conditions of their development, managers and lawyers of various companies are actively looking for new ways, methods, methods, technologies and develop innovative competitive models based on them, constantly adapting to changes and even , stimulating such changes. Therefore, the presence of unique assets and advantages of the company helps to consolidate its positions on the market. In order to win the struggle of manufacturing enterprises for the consumer, to draw his attention to the product of a particular business, more and more efforts are being made in the field of development and effective application of one of these assets – the brand. It was found that according to the latest concept of innovative branding – brand leadership – the main goal of brand management models is the development and growth of the value of the main intangible asset of the organization – brand capital, which is determined by the value of the brand.